Akurasi Skor Siriraj dalam Memprediksi Jenis Stroke - Berna Detha Meilyana; Astri Yunita (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2023)
: Stroke is a clinical condition that can cause decreased nerve function which is affected by injury to the central nervous system. Stroke causes high rates of death and disability. Precise and careful initial examination is an action that affects management. There is a scoring tool that can be used to help establish a diagnosis and predict the type of stroke if there is no standard CT scan available in the hospital emergency department or if it is available but its use is still not optimal. Siriraj score is a scoring that can be helpful and reliable to determine the type of stroke. This study aims to determine the accuracy of the Siriraj score in predicting the type of stroke in patients with. In this study use analytical observational method with cross sectional design. The sample selection used purposive sampling with a total of 100 stroke patients. Observations were made using the Siriraj score. Demographic characteristics of patients who had a stroke aged 54-64 years and 67% of strokes were experienced by male patients.The results showed that the Siriraj score to determine ischemic stroke had a sensitivity of 94.5%, specificity 92.5%, PPV 97.1%, NPV 86.2% and accuracy 94%, while to determine hemorrhagic stroke had a sensitivity of 100%, specificity 100%, (PPV) 100%, (NPV) 100% and 100% accuracy. Determining the type of stroke quickly and accurately requires Siriraj stroke scoring that can be done by nurses for providing stroke management. The Siriraj score can be used to determine ischemic and hemorrhagic stroke.